2(y-4)=-4(y+8)

Simple and best practice solution for 2(y-4)=-4(y+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(y-4)=-4(y+8) equation:


2(y-4)=-4(y+8)

We simplify the equation to the form, which is simple to understand
2(y-4)=-4(y+8)

Reorder the terms in parentheses
+(+2y-8)=-4*(y+8)

Remove unnecessary parentheses
+2y-8=-4+*(+y+8+)

Reorder the terms in parentheses
+2y-8=+(-4y-32)

Remove unnecessary parentheses
+2y-8=-4y-32

We move all terms containing y to the left and all other terms to the right.
+2y+4y=-32+8

We simplify left and right side of the equation.
+6y=-24

We divide both sides of the equation by 6 to get y.
y=-4

See similar equations:

| -5x-9x=98 | | 1.4-.04x=5.20 | | -2u/5=-10 | | 44-6x=3x+23 | | 25=3+3n-5 | | 9x+12=-177 | | 9/25w^4+w^2z^3+1/9z^6 | | 2x/5-x/2 | | -1x+15+3x+15=-4 | | x(9x-5)=13 | | -5a-10=10 | | 0.12(y-7)+0.04y=0.10y-0.9 | | x(x+2)-3x=4+y | | (2/3)x-(1/6)=(1/2)x+(5/6) | | 9r+5=4r+5 | | n+n+2+n+4+n+6+n+8=1095 | | -7x=175 | | n+n+1+n+2+n+3=60 | | 4[2x-(3-x)+5]=-7-2 | | 9x-20-61+13x=17x+57-14x+71 | | 20d+12-12d=-43 | | 1/4=-1/85/4X | | 6k^2+13k-5a^2=0 | | 22=-11r | | 1/16=-x/11 | | -3+p=7 | | 4/11-6 | | -3+p= | | 4/5x-6=5 | | 6*5+4*10=10c | | (5/2)t-t=3+(3/2)t | | (-2/3)t-3=-5 |

Equations solver categories